PELATIHAN GEOGEBRA UNTUK GURU-GURU SMA DI KALIMANTAN BARAT - Bernadeta Wuri Harini; Djoko Untoro Suwarno; Martanto Martanto; Wiwien Widyastuti; Theresia Prima Ari Setiyani; Lusia Krismiyati Budiasih (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2022)
Mathematics and Physics are subjects that are not only difficult for students but also difficult for teachers. To make it easier to understand the material, Geogebra software is used. In this community service, Geogebra training was provided for high school teachers who are Mathematics and Physics teachers in West Kalimantan. The training was conducted online involving 10 lecturers and 5 assistants. The training consisted of 4 sessions carried out over 2 days which was attended by 31 teachers of Mathematics and Physics. The training is divided into 2 classes to be more effective. From the training results, there was an increase in the ability to use Geogebra by 38.05%. The average level of participant satisfaction with the implementation of the study is 4.15 on (a scale of 5)